A chegada da Fiat no Brasil: uma nova entrante no oligopolizado mercado automobilístico brasileiro (1970 a 1973) - Pedroni, Marcos Olmos (2019)
This study aimed to investigate the arrival of Fiat in the oligopolized brazilian automobile market in the early 1970s. Fiat was the first major automaker to establish a new operation in the country since the implementation of the automobile industry, which occurred in the second half of the 1950s, during the administration of Juscelino Kubistchek. The company decided to establish its factory in Minas Gerais, while the other major automakers were all in the state of Sao Paulo. We will analyze the reasons for the Italian company to come to Brazil when the world's largest automakers were already operating here; the choice of Minas Gerais for the construction of its factory; the agreements made with the Minas Gerais State and Municipality of Betim, the city chosen by Fiat. In the end, we have looked at the choice criteria for the Fiat 127, a car made in Italy that would later give rise to the Fiat 147. Our main source of research were documents collected at the Centro Storico Fiat, where the company keeps its historical records, located in Turin, Italy. Another important source of research was the mainstream press, represented by the newspapers O Estado de S. Paulo and Estado de Minas